FEATURES OF MORPHOLOGICAL HOMONYMS IN KYRGYZ LANGUAGE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In this article features of homonyms in Kyrgyz language and their formation were analyzed. Homonyms are classified in accordance with parts of speech and are formed with the help of suffixes, which was proved by a number of examples in the research.
Keywords: homonym, polysemy, morphology, vocabulary, grammar, part of speech, stem, suffix